The rootstock shape microbial diversity and functionality in the rhizosphere of Vitis vinifera L. cultivar Falanghina - Zuzolo, Daniela; Ranauda, Maria Antonietta; Maisto, Maria; Tartaglia, Maria; Prigioniero, Antonello; Falzarano, Alessandra; Marotta, Giuseppe; Sciarrillo, Rosaria; Guarino, Carmine (Frontiers in Plant Science, 2023)
The rhizosphere effect occurring at the root-soil interface has increasingly been shown to play a key role in plant fitness and soil functionality, influencing plants resilience. Here, for the first time, we investigated whether the rootstock genotype on which Vitis vinifera L. cultivar Falanghina is grafted can influence the rhizosphere microbiome. Specifically, we evaluated to which extent the 5BB and 1103P rootstocks are able to shape microbial diversity off rhizosphere environment. Moreover, we explored the potential function of microbial community and its shift under plant genotype influence.We investigated seven vineyards subjected to the same pedo-climatic conditions, similar age, training system and management and collected twelve rhizosphere soil samples for metagenomic analyses and composite soil samples for physical-chemical properties. In this study, we used 16S rRNA gene-based metagenomic analysis to investigate the rhizosphere bacterial diversity and composition. Liner discriminant analysis effect size (LEFSe) analysis was conducted for metagenomic biomarker discovery. The functional composition of sampled communities was determined by using PICRUSt, which is based on marker gene sequencing profiles. Soil analyses involved the determination of texture, pH, Cation Exchange Capacity (CSC), Organic Carbon (OC), electrical conductivity (EC), calcium (Ca), magnesium (Mg), potassium (K) content, Phosphorous (P), nitrogen (N). The metagenomic data showed that the bacterial alpha-diversity (Observed OTUs) significantly increased in 1103P rhizosphere microbiota. The latter revealed that soil was quite homogenous. Irrespective of cultivar, ProteobacteriaPseudomonadota was the dominant phylum, followed by ActinobacteriaActinomycetota > Bacteroidota Bacteroidetes > ThermoproteotaCrenarchaeota. Proteobacteria. However, ActinobacteriaActinomycetota was the major marker phyla differentiating the rhizosphere microbial communities associated with the different rootstock types. At the genus level, several taxa belonging to ActinobacteriaActinomycetota and Alphaproteobacteria Alphaproteobacteria generaclasses were enriched in 1103P genotype rhizosphere. Investigating the potential functional profile, we found that most key enzyme-encoding genes involved in N cycling were significantly more abundant in 5BB rootstock rhizosphere soil. However, we found that 1103P rhizosphere was enriched in genes involved in C cycle and Plant Growth Promotion (PGP) functionality. Our results suggest that the different rootstocks are not only to recruit specific bacterial communities, but also specific functional traits within the same environment.